Maintenance planning for Masjid Kariah in Malaysian perspective: a systematic literature review and PRISMA method - Yusof, Azhar; Mohamad Ridzuan; Ismail, Faridah; Hashim, Siti Fatimah (UiTM Press, 2025)
The maintenance planning of Masjid Kariah in Malaysia is critical for ensuring the functionality, safety, and spiritual integrity of these community-focused institutions. Despite their significance, these mosques face numerous challenges, including limited financial resources, insufficient skilled labour, and the need to balance between traditional architectural elements and modern building techniques. This study has conducted a systematic literature review, by employing the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method, to examine the maintenance challenges of Masjid Kariah in Malaysia and to propose contextually appropriate strategies to improve their maintenance practices and long-term community function. By synthesising the findings of previous studies, this aimed to fill the gap in the literature concerning the unique maintenance requirements of Masjid Kariah. This review has identified several key issues, such as inadequate facilities, poor monitoring systems, and the lack of strategic planning in rural mosques, which often suffer from neglect. The findings of this review have also underscored the need for a more systematic and culturally sensitive maintenance strategy to address the specific challenges faced by these mosques in Malaysia.